Trajectories into gang membership: Exploring risk exposure, protective factors and the factors motivating involvement in devil-worshipping gangs - Phillips, Ashwill R. (Social Work/Maatskaplike Werk, 2025)
Gangs represent a complex phenomenon, emerging in response to social exclusion, limited opportunities and systemic inequalities. In South Africa, gang-related crime is rife, impacting on individuals, families and broader society. Gang practices in the Free State province allegedly incorporate elements of the occult, including devil-worshipping and witchcraft, generating fear within affected communities. These gangs engage in spiritually-motivated crimes including blood sacrifice, animal slaughter and communication with demons. Drawing on qualitative data obtained from interviews with detained gang members, non-gang-affiliated offenders and service providers, the paper explores key factors motivating membership as well as the protective factors which safeguard against gang involvement. Moreover, the existence of ‘devil-worshipping’ gangs and the prominent risks and protective features in this regard are explored. The findings highlight the need for protection, poverty and peer influence as pertinent factors perpetuating gang membership, while creating prosocial activities, employment and gang-awareness were noted as key protective factors. Understanding risk exposure, gang trajectories and factors that enhance resilience from the lived experience of offenders serve to humanise the gang issue and assists social workers and other stakeholders to strengthen support services for vulnerable youths, develop targeted interventions, refine policies and systemic responses, and incorporate relevant protective factors when designing or facilitating programmes within gang-prone communities.